KARAKTERISTIK GEOMORFOLOGI DAERAH PASIRIPIS DAN SEKITARNYA, KECAMATAN SURADE, GEOPARK CILETUH PALABUHANRATU: GEOMORPHOLOGICAL CHARACTERISTICS OF PASIRIPIS AND SURROUNDING REGIONS, SURADE DISTRICT, GEOPARK CILETUH PALABUHANRATU - Daffa Rafli; Santi Dwi; Mega Fatimah (Universitas Trisakti, 2024)
The research was conducted in Pasiripis area, Surade sub-district, Sukabumi district, West Java province, which is part of the Ciletuh Palabuhanratu Geopark with the aim of identifying the characteristics of developing geomorphological Units, and classifying the distribution of lithological constituents in each unit. Identification of geomorphological characteristics is based on remote sensing analysis of DEM SRTM Data which is then processed in Arcgis Software, Global Mapper and field observations are made in mapping geomorphology and lithology distribution according to scientific standards to match the data from remote sensing analysis. The research findings are in the form of distribution maps based on morphographic aspects, flow pattern maps, landform maps, slopes and geomorphological components in geomorphological maps. The study area is divided into lowlands and low hills with a developed drainage pattern that is dendritic, sub-dendritic, and parallel. In the morphometric aspect, the slopes are flat or almost flat, very gentle, gently sloping, and slightly steep. The morphogenetic aspect in Pasiripis area shows the existence of endogenous processes, such as tectonism and volcanism activities, as well as exogenous processes, such as weathering, erosion, and dissolution. The lithology of the study area consists of limestone, sandstone, and tuff. Based on the geomorphological reconstruction aspect, the characteristics of Pasiripis area in Surade sub-district can be classified into five geomorphological unit, namely flat denudational lowland, gentle denudational lowland, gentle maritime lowland, gentle denudational lowland hills, and slightly steep denudational lowland hills.